Sustainable saline wastewater treatment using eutectic freeze crystallization : Recent advances, challenges and future prospects - Winnie Huong, Tien Ting; Ivy Tan, Ai Wei; Shanti Faridah, Salleh; Noraziah, Abdul Wahab; Mohd Farid, Atan; A. A., Abdul Rahman; Kong, S. L.; Lam, L. S. (Elsevier B.V., 2024)
The increase in global population, industrialization and urbanization has resulted in a corresponding increase in saline wastewater, causing escalating environmental and health concerns. The increasing volume of saline wastewater generated by various industries poses significant disposal challenges, and regulatory pressures and public awareness are driving the need for innovative and environmentally friendly treatment techniques. In response to these challenges, eutectic freeze crystallization (EFC) has emerged as a promising innovative solution, owing to its energy-efficient nature and ability to recover salts. This comprehensive review provided insights into the bibliometric analysis of EFC technology, offering an overview of the current state-of-the-art research in the EFC process for saline wastewater treatment. In comparison between EFC and other existing saline wastewater treatment processes, EFC holds remarkable advantages in terms of liquid waste minimization, valuable resource recovery and without salinity restriction. Besides, the advancement and applications of EFC in the treatment of various type of saline wastewater were also discussed, indicating a growing interest among researchers due to its high versatility. While successful applications of EFC have been highlighted, the challenges such as ice scaling issue and complexity of multi-component wastewater treatment using EFC still persist. These challenges bring directions for future prospects in EFC research, underscoring the need for more research and development efforts to enhance the effectiveness and economic benefits of EFC technology for its widespread application in treating industrial saline wastewater.